2009
DOI: 10.1002/ejsp.703
|View full text |Cite
|
Sign up to set email alerts
|

I think I like you: Spontaneous and deliberate evaluations of potential romantic partners in an online dating context

Abstract: The present research examined processes of impression formation within an online dating context. Across two studies, female participants formed impressions of a potential partner based on an online dating profile containing information about the target's facial attractiveness and self-described ambition. Afterwards, deliberate evaluations of the target were assessed with a self-report measure and spontaneous evaluations were measured with an affective priming task. The results showed that deliberate evaluation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 48 publications
0
32
0
Order By: Relevance
“…In most romantic contexts, people make partner selections based on a rich wealth of Figure 5. Examination of the correlations between each model shows the strongest correlations are between (1) warmthtrustworthiness and approachability; (2) status-resources and dominance; and (3) information that includes facial appearance (Fletcher et al, 2014;Sritharan, Heilpern, Wilbur, & Gawronski, 2010;Walster et al, 1966). These are presented in terms of the strength of correlation for all participants rating all faces.…”
Section: Discussionmentioning
confidence: 99%
“…In most romantic contexts, people make partner selections based on a rich wealth of Figure 5. Examination of the correlations between each model shows the strongest correlations are between (1) warmthtrustworthiness and approachability; (2) status-resources and dominance; and (3) information that includes facial appearance (Fletcher et al, 2014;Sritharan, Heilpern, Wilbur, & Gawronski, 2010;Walster et al, 1966). These are presented in terms of the strength of correlation for all participants rating all faces.…”
Section: Discussionmentioning
confidence: 99%
“…They were then informed that they would examine an online dating profile that had ostensibly been submitted to a developing campus dating service and would answer several questions concerning the person described by the profile. The dating profile was adapted from Sritharan et al (2010), including basic information pertaining to the user's demographics. The profile did not contain a photograph, however, so that we could more cleanly assess the effect of humor on attraction without the noise introduced by physical attractiveness.…”
Section: Methodsmentioning
confidence: 99%
“…A second study revealed that men and women rate humorous comments made by attractive targets as funnier than identical comments made by less attractive targets. People have strongly positive explicit and implicit responses to physically attractive individuals (Sritharan, Heilpern, Wilbur, & Gawronski, 2010), so it is not surprising that both men and women use humor production and appreciation to convey their interest in especially attractive targets. A third study found that third-party observers perceive men's humor initiation and women's positive responses to humor as indicative of romantic interest.…”
mentioning
confidence: 99%
“…Ancestrally, women could have ascertained this by a man's potential for accruing resources, which in the modern environment equates with monetary resources (Symons, 1979;Buss, 2003). Ambition is correlated with the drive and ability to acquire resources, and women prefer long-term partners who are ambitious (e.g., Buss, 1989;Buss and Barnes, 1986;Buss et al, 2001;Kenrick et al, 1993Kenrick et al, , 1990 and will even prefer ambitious yet physically unattractive men to nonambitious yet physically attractive men (Sritharan et al, 2010;Townsend and Wasserman, 1998;Wilbur and Campbell, 2010). Women who selected men who could accrue resources as partners would have produced more offspring who survived than women who chose other men.…”
Section: Long-term Matingmentioning
confidence: 99%